The effect of a thiol-containing organic molecule on molybdenum adsorption onto pyrite. (1st February 2016) - Freund, Carla; Wishard, Anthony; Brenner, Ryan; Sobel, Marisa; Mizelle, Jack; Kim, Alex; Meyer, Drew A.; Morford, Jennifer L.
Abstract: The effect of a small thiol-containing organic molecule on the adsorption of Mo to pyrite was investigated through the use of equilibration experiments with molybdate (MoO4 2− ), tetrathiomolybdate (MoS4 2− ), and 2-mercaptopropionic acid (2MPA). MoO4 2−, MoS4 2−, and 2MPA individually adsorb to pyrite through the formation of specific interactions with the mineral surface. In select combination experiments, 2MPA effectively out-competes MoO4 2− for pyrite surface sites, which is indicative of the relatively weaker MoO4 2− -pyrite interactions. Results suggest that the presence of 2MPA on the pyrite surface would inhibit MoO4 2− access to catalytic mineral surface sites for the transformation of MoO4 2− to MoS4 2− . In contrast, thiols are not expected to be an obstacle to Mo uptake once the "switch point", or the critical H2 S concentration required for the formation of MoS4 2−, has been surpassed. This is due to the stronger adsorption of MoS4 2− to the pyrite surface. EXAFS results support weak specific interactions with little change to the MoO4 2− environment upon adsorption to pyrite. In contrast, larger changes to the Mo–S internuclear distances during MoS4 2− adsorption to pyrite support a more substantial structural change upon adsorption. MoS4 2− is able to bind to both the pyrite surface and a thiol-containing organic molecule to form a ternary structure on the pyrite surface, and may provide for a molecular-level connection between Mo and thiol-containing organic molecules. Mo(VI) is reduced to Mo(IV) during MoS4 2− adsorption to pyrite as a result of ligand-induced reduction, thereby confirming that the thiolated form of Mo is necessary for Mo reduction.